АКТУАЛЬНОСТЬ ИЗУЧЕНИЯ ШКОЛЬНОГО КУРСА ФИЗИКИ - Ешбаева, М. (SCIENCE and SOCIETY, 2024)
This article analyzes the need for basic knowledge of physics for everyone in the modern world and indicates the need to integrate technology into the educational process in physics. The issue of improving accessibility and increasing interest in physics among students in order to improve educational results is covered. It also highlights the role of physics in technological advances and addresses the problem of declining student interest in physics, emphasizing the importance of adapting educational methods to modern conditions.